Characterization of the charge transfer luminescence of the [WO6]6− octahedron in Ca3WO6 and the [WO5]4− square pyramid in Ca3WO5Cl2. Issue 39 (28th September 2022) - Kitagawa, Yuuki; Takemura, Shota; Hirai, Daigorou; Hiroi, Zenji; Ueda, Jumpei; Tanabe, Setsuhisa
Abstract : The five-fold square pyramid caused by Cl − introduction brings about an inconsistent energy shift of the charge transfer excited states. Abstract : Charge transfer (CT) luminescence of different types of polyhedra, [WO5 ] 4− in Ca3 WO5 Cl2 and [WO6 ] 6− in Ca3 WO6, is characterized by spectroscopic experiments and ab initio calculations. According to the geometry optimization, W 6+ ions form five-fold [WO5 ] 4− square pyramids in Ca3 WO5 Cl2 because of a large interatomic distance between W 6+ and Cl − of 3.266 Å. The analysis of the density of electronic states reveals the ionic character of Cl − ions to the W 6+ ions in the Ca3 WO5 Cl2 lattice, resulting in the observed broad luminescence band peak at 488 nm of the single-crystal Ca3 WO5 Cl2 sample being assigned to the CT transition in the [WO5 ] 4− square pyramid. Compared with the [WO6 ] 6− octahedron in Ca3 WO6, the [WO5 ] 4− square pyramid shows an inconsistent CT energy shift: higher CT absorption and lower luminescence energies. The larger bandgap brings about higher absorption energy due to the structural and compositional features of the orthorhombic Ca3 WO5 Cl2 . The redshifted CT luminescence band and small activation energy for the thermal quenching of the Ca3 WO5 Cl2 sample are explained, assuming that the CT states of the anisotropic [WO5 ] 4− square pyramid take a larger offset in the configurational coordinate diagram than the [WO6 ] 6− octahedron.